Adaptive Education Technologies to Train Russian Teachers to Use E-learning. Issue 10 (2016) - Barakhsanova, Elizabeth Afanasyevna; Savvinov, Vasily Mikhaylovich; Prokopyev, Mikhail Semenovich; Vlasova, Elena Zotikovna; Gosudarev, Ilya Borisovich
No abstract available